The struggle over the character of social services: conceptualising hybridity and power. Issue 1 (2nd January 2022) - Timor-Shlevin, Shachar; Benjamin, Orly
ABSTRACT: Extensive critical literature has pointed to the corrosive effects of managerialism and New Public Management (NPM) on social services and demonstrated how its local versions dominate policymaking. Challenging such critical views, another stream of thought has emerged, emphasising the way in which policymaking could take a hybrid shape, reflecting the mutual contribution of NPM and critical professionalism to the shaping of social services. However, the hybrid proposition lacks a nuanced formulation of the power relations between these contesting standpoints. Here, we offer to add this missing aspect by investigating senior public service managers' encounter with the critical professional standpoint. Based on the analysis of 16 interviews with senior administrators shaping Israeli social services for people living in poverty, we identify the operation of three modes of power exertion, namely, conditional funding, suspicion, and rejection to articulate the integration of power dynamics into the conceptualisation of hybridity.